PERAN ILUSTRASI BERTEMA INDONESIA PADA PRODUK MINUMAN TERHADAP RESPON EMOSI KONSUMEN DALAM MEMBELI DAN MEMAHAMI PRODUK - Ni Putu Emilika Budi Lestari; Ngurah Adhi Santosa; Annisa Rohimah Suharno (Jurnal Bahasa Rupa, 2022)
This study aims to determine the effect of visual elements in the form of illustrations with Indonesian themes and Indonesian local wisdom on the packaging of popular beverage products in the eyes of consumers, both in terms of sales and their impact on the emotional response of consumers as Indonesians. Through the use of illustrations on packaging, producers also want to convey certain messages to their consumers. Because in fact, the appearance of an attractive packaging will give a distinct impression and emotional closeness for consumers in determining their decision to buy or not to buy a product. The research method was carried out qualitatively through literature and questionnaires. The theory used in this research is packaging design theory, concerning the visual effect of packaging on consumer buying interest. In addition, the author also uses illustration theory to identify illustration techniques and Roland Barthes 'semiotic theory to find out how illustration affects consumers' emotional responses and how consumers perceive related illustrations. The result of this research is that the use of Indonesian themed illustrations on beverage product packaging can be said to increase consumer emotionality to buy products, based on eye-catching illustration factors in terms of style, selection of illustration objects, colors and themes. In addition, the packaging design with illustrations on the Indonesian theme is interesting to collect as memorabilia.